2013
DOI: 10.1007/s11033-013-2572-9
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CBL-interacting protein kinase (CIPK6) is involved in plant response to salt/osmotic stress and ABA

Abstract: The CBL-CIPK signaling pathway represents a central and critical signaling system involved in plant response to abiotic stress and hormone signaling. In this study, we focused on AtCIPK6 gene, which have been shown to be required for development and salt tolerance in Arabidopsis, but the transcriptional regulatory mechanism of AtCIPK6 gene and whether it plays a role in ABA signaling is still unknown. Here, we showed that in addition to its expression induced by salt and drought stress, the transcripts of AtCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 43 publications
1
51
0
2
Order By: Relevance
“…This network has been demonstrated to function in various biotic and abiotic stresses, including high salinity, osmotic stress, drought, cold, ABA and fungi attack [83, 84]. CIPK6 in Arabidopsis is induced by drought and ABA, and overexpression of this gene improves the salt tolerance of Arabidopsis plants [85]. Ectopic expression of an apple CIPK, MdCIPK6L , in Arabidopsis , also confers multiple stress tolerance of the transgenic plants [86].…”
Section: Discussionmentioning
confidence: 99%
“…This network has been demonstrated to function in various biotic and abiotic stresses, including high salinity, osmotic stress, drought, cold, ABA and fungi attack [83, 84]. CIPK6 in Arabidopsis is induced by drought and ABA, and overexpression of this gene improves the salt tolerance of Arabidopsis plants [85]. Ectopic expression of an apple CIPK, MdCIPK6L , in Arabidopsis , also confers multiple stress tolerance of the transgenic plants [86].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of 946 probe sets changed in both Zhong G5 and Zhong 07 after salt stress treatment. Many of these identified differentially expressed transcripts (fold change > 2 and p-value < 0.05) were previously reported to be involved in the salt stress response, such as orthologs of SOS3 [19], ABI1 [52], STZ/ZAT10 [53], CIPK6 [54,55], and WRKY40 [56]. To validate the microarray results, we selected some probe sets that were found to be differentially expressed based on our microarray analysis.…”
Section: Genes That Are Differentially Expressed In the Salt-sensitivmentioning
confidence: 99%
“…GO analysis showed that the GO terms "response to water", "response to hormone stimulus", and "transcription factor activity" were significantly enriched (Table 1). After a 3 h exposure to 150 mM NaCl, some genes related to salt stress and osmotic stress were upregulated; these genes include orthologs of Arabidopsis ABI1 [52], STZ/ZAT10 [53], SOS3 [19], and CIPK6 [54,55]. A. thaliana SOS3 has been described as a unique calcium-binding protein during the plant's response to salt stress [19].…”
Section: Identification Of Candidate Salt Tolerance-related Transcripmentioning
confidence: 99%
“…Recently, a novel mechanism by which activity of CBL-CIPK complexes is regulated has been dissected [50]. CBL-CIPK complexes are involved in mediation of plant response to environmental cues, including drought [51], cold [51,52], salinity [53,54] and osmotic stress [55]. In addition to the abiotic stresses, the involvement of CBL-CIPK network in regulation of uptake and translocation of mineral elements is also reported.…”
Section: Among the [Ca 2+ ] C -Induced Downstream Components Calcinementioning
confidence: 99%